A portable smartphone-based colorimetric sensor for rapid determination of water content in ethanol. (January 2020) - Shahvar, Ali; Shamsaei, Danial; Saraji, Mohammad
Graphical abstract: Highlights: A new smartphone-based colorimetric sensor was introduced. The method was successfully applied for water assaying in ethanol samples. The method was simple and cost-effective with no need for a skilled operator. The sensor was portable with the capability of field analysis. Abstract: Herein, a simple, low cost and portable smartphone-based colorimetric sensor was introduced for rapid determining water content in ethanol. The method was based on the color-changing of cobalt(II) chloride in ethanolic solution followed by sensing and data processing using a colorimetric sensor. The sensor consisted of a smartphone as a detector, illumination source and data processor, and a lab-made box to hold the smartphone and sample cell. The effect of key experimental factors on the response was investigated. A linear response in the range of 0.05–2.00% v/v was observed with the detection and quantification limits of 0.02 and 0.05% v/v, respectively. The sensor was successfully applied for the determination of water content in several ethanolic solutions with recoveries higher than 88%. The method was an environmentally and economic friendly technique since it consumed only 78 mg of CoCl2 per 100 tests and required about 30 s for each assay.